2014
DOI: 10.1039/c4cc01012d
|View full text |Cite
|
Sign up to set email alerts
|

An AIE-active luminophore with tunable and remarkable fluorescence switching based on the piezo and protonation–deprotonation control

Abstract: A novel luminophore TPENSOH was facilely synthesized from the building blocks of tetraphenylethylene and 6-hydroxylbenzothiazole and exhibited unique AIE properties. This new dye was found to show a remarkable and reversible four-color switching based on a single molecule in the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(66 citation statements)
references
References 22 publications
(3 reference statements)
0
65
0
1
Order By: Relevance
“…Compounds 4-(1,2,2-triphenylvinyl)benzaldehyde (5) [15] and 4-(1,2,2-triphenylvinyl)aniline (7) [16] were prepared according to literature methods. All other chemicals and reagents were purchased from J&K Scientific Ltd., and used as received without further purification.…”
Section: Materials and Instrumentsmentioning
confidence: 99%
“…Compounds 4-(1,2,2-triphenylvinyl)benzaldehyde (5) [15] and 4-(1,2,2-triphenylvinyl)aniline (7) [16] were prepared according to literature methods. All other chemicals and reagents were purchased from J&K Scientific Ltd., and used as received without further purification.…”
Section: Materials and Instrumentsmentioning
confidence: 99%
“…Some serendipitous examples exhibiting tricolored emission switching have been reported including liquid crystal mixture with 9,10‐bis(phenylethynyl)anthracene by Sagara and Kato, twisted donor acceptor type MC luminogen by Ma and co‐workers, tetraphenylethylene linked rhodamine B by Jia and co‐workers, and so forth. Chi and co‐workers reported one tetraphenylethene derivative with 6‐hydroxylbenzothiazole, whose emission can be tuned among four colors through mechanical stimulus protonation and deprotonation, while the chemical structure is changed upon protonation . Sagara and Weder achieved modulation of one cyano‐substituted oligo( p ‐phenylene vinylene) among five emissive states .…”
Section: Introductionmentioning
confidence: 99%
“…The aim of introducing 6-hydroxylbenzothiazole was to achieve as ite specific in response to acid ( Figure 14). [27] 17 wasA IE active and showed at etracolor change based on piezo and protonation-deprotonation control. As shown in Figure 14, an as-prepared powder of 17 (B 1 )e xhibited strong blue-light emission centered at 454 nm.…”
Section: Multicolor Switchingina Ie Moleculesmentioning
confidence: 99%
“…Adapted with permission from Ref. [27].C opyright 2014, Royal SocietyofC hemistry. ChemPhysChem 2015ChemPhysChem , 16,1811ChemPhysChem -1828 www.chemphyschem.org Weng et al has also observed similar phenomena.…”
Section: Multicolor Change Owing To Mechanical Control Of Chemical Stmentioning
confidence: 99%